Language as Resistance: A Postcolonial Approach to the Use of Nation Language as Cultural Translation in Grace Nichols' Poems - Romariz, Leticia (Em Tese, 2022)
he colonial enterprise transformed our world and the way we perceive it and ourselves. Our structures of knowledge were reshaped and a hierarchic division of the world and of peoples was established. The postcolonial studies arise in this context to deal with such effects (ASHCROFT ET AL, 2013, p. 108) and with the many forms of resistance that now take place. One of them is the use of language as resistance. Since the colonial intellectual transformation occurred mainly through language, it only makes sense that the former colonized subjects make use of it as well in their subversive enterprises. This article analyzes the development and use of nation language (BRATHWAITE, 1996) as resistance against the effects of colonialism in the Caribbean author Grace Nichols’s book The Fat Black Woman’s Poems (1984). Although literature and language may not be able to transform reality, they are able to create alternative narratives with more inclusive futures.